Neuromuscular strategies of the ankle joint during running: Does strength matter? - Enders, H.; Lucas-Cuevas, A.; Baltich, J.; Nigg, B. M. (International Calgary Running Symposium, August 14-17, 2014, 2014)
Background: Ankle injuries are a common sports injury (1). Muscle weakness has been identified as one risk factor for ankle injuries (2, 3). In addition to reduced force production, muscle weakness may change neuromuscular strategies used during running itself. The purpose of this study was to quantify neuromuscular strategies during running in individuals with strong and weak ankle muscles. Methods: Eighteen subjects were divided into two groups based on their isometric plantarflexion torque. EMG of five ankle muscles was collected during maximum voluntary contractions (MVC). Subjects also performed 10 heel-toe running trials while EMG was measured. Root mean square (RMS) values were calculated for the running EMG for a time window of 300ms around heel-strike and normalized to the RMS of the MVC. A support vector machine was used to determine the most prominent differences and calculate the classification rate between both groups. Results: A significant mean classification rate (p < 0.05) of 71% was achieved across all subjects. While the normalized RMS showed no significant differences for individual muscles (Figure 1A), the SVM revealed a significant difference between both groups. The strong group showed more activity for the tibialis anterior and peroneus longus and less activity for the triceps surae (TS). Discussion: Individuals with ankle weakness use a dominant TS strategy during running while stronger individuals show increased activity in smaller muscles. In addition to lower force production capacity, ankle weakness changes neuromuscular strategies during running. Ankle strengthening may be a useful tool to alter neuromuscular strategies for dynamic movements such as running.